1982
DOI: 10.1007/bf00151609
|View full text |Cite
|
Sign up to set email alerts
|

Study of the post-flare loops on 29 July 1973

Abstract: We present revised values of temperature and density for the flare loops of 29 July 1973 and compare the revised parameters with those obtained aboard the SMM for the two-ribbon flare of 21 May 1980. The 21 May flare occurred in a developed sunspot group; the 29 July event was a spotless two-ribbon flare. We find that the loops in the spotless flare extended higher (by a factor of 1.4-2.2), were less dense (by a factor of 5 or more in the first hour of development), were generally hotter, and the whole loop sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 14 publications
3
18
0
1
Order By: Relevance
“…Prior to these observations, the duration of reconnection processes was usually inferred from either the time over which chromospheric ribbons kept separating or the time over which hot loops kept rising to higher altitudes. From the time history of the H ribbon separation and of the hot loop heights for the 1973 July 29 flare that was considered to be an ideal example for a case study (see, e.g., Moore et al 1980;Svestka et al 1982), reconnection was recognized to go on for at least %10 hr. Hence, UVCS data considerably extended the time interval over which reconnection was observed to operate.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to these observations, the duration of reconnection processes was usually inferred from either the time over which chromospheric ribbons kept separating or the time over which hot loops kept rising to higher altitudes. From the time history of the H ribbon separation and of the hot loop heights for the 1973 July 29 flare that was considered to be an ideal example for a case study (see, e.g., Moore et al 1980;Svestka et al 1982), reconnection was recognized to go on for at least %10 hr. Hence, UVCS data considerably extended the time interval over which reconnection was observed to operate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned data, the 29 July, 1973 flare comprises an ideal example for a case study because our knowledge of the plasma physical conditions at the tops of the flare loops now appears to be fairly reliable (Svestka et aL, 1982). The latitude and size of this flare suggest that the eighth lobe of a Pls-field is appropriate.…”
Section: The 29 July 1973 Flarementioning
confidence: 96%
“…Moreover, it was found that the cooling time can be estimated by using the velocity and the width of the flare ribbons (Švestka et al 1982;Priest & Forbes 2002). The PFLs are observed expanding in a particular wavelength during the 8 cooling process.…”
Section: Cooling Process Of Dpflsmentioning
confidence: 99%